Compulsory education at the secondary level in Latin America. Convergences and divergences in five Countries - María Consuelo Ruiz; Susana Schoo (FahrenHouse, 2014)
This paper shows the analysis of different ways in which Latin American countries have faced the reform processes in the last 20 years. For this purpose, the ways how Argentina, Brazil, Chile, Paraguay and Uruguay have extended compulsory education are taken as analyzer. Firstly, we contextualize the socio demographic situation of the studied countries. Secondly, we make a brief review of the schooling processes in these countries and their outstanding historical trends related to the extension of compulsory education. Thirdly, we describe the secondary education organization in the context of national reforms of the last twenty years. Finally, we analyze the ways of secondary level admission and graduation in each country and some educational indicators with the aim of visualizing some decisive aspects in compulsory secondary education. Received: 07/10/2013 / Accepted: 29/11/2013 How to reference this article Ruiz, M. C., Schoo, S. (2014). La obligatoriedad de la educación secundaria en América Latina. Convergencias y divergencias en cinco países. Foro de Educación, 12(16), pp. 71-98. doi: http://dx.doi.org/10.14516/fde.2014.012.016.003